Effect of Guanidinoacetic Acid Supplementation on the Performance of Calves Fed Milk Replacer - Kathryn J. Hazlewood; Charles A. Zumbaugh; Cassandra K. Jones; Emily M. Atkinson; Hannah L. R. Tingler; Vivienne K. Inhuber; Micheal J. Brouk; Reshma M. Antony; Evan C. Titgemeyer (Animals)
Guanidinoacetic acid (GAA) is the direct precursor to creatine, which serves as an energy reserve mechanism in the body. We evaluated the effects of GAA supplementation on the growth performance of calves fed milk replacer. Forty-five Holstein–Angus steer calves (40.9 kg, approximately 1 week old) were assigned to 1 of 3 treatments to assess growth performance and data from 41 calves were analyzed. Treatments were provided in the milk replacer for 42 d and included 0, 1, or 2 g GAA/d. Calves were fed 2.84 L milk replacer twice daily with ad libitum access to starter feed and water. Treatments ended on day 42 prior to a 17-day weaning period. Supplementation of GAA increased (p < 0.01) plasma concentrations of GAA (0.42, 0.51, and 0.67 mg/L for 0, 1, and 2 g GAA/d, respectively) and creatine (18.7, 22.1, and 24.4 mg/L for 0, 1, and 2 g GAA/d, respectively). Bodyweight tended to linearly increase (p = 0.09) with increasing GAA on d 59 (91.2, 98.3, and 98.6 kg for 0, 1, and 2 g GAA/d, respectively). Daily gains from day 0 to 59 tended to increase with GAA provision (p = 0.09; 0.86, 0.97, and 0.98 kg/d for 0, 1, and 2 g GAA/d, respectively). Starter feed dry matter intake tended to linearly increase (p = 0.06) with GAA supplementation (0.201, 0.278, and 0.286 kg/d for 0, 1, and 2 g GAA/d, respectively). Treatments providing 1 and 2 g GAA/d affected performance similarly. No differences among treatments were observed for health (respiratory and fecal) scores during the application of treatments or during the subsequent weaning period. The inclusion of GAA in milk replacer tended to increase the gain of calves, and this was associated with elevated starter feed intake.